Atrophy Resistant vs. Atrophy Susceptible Skeletal Muscles: “aRaS” as a Novel Experimental Paradigm to Study the Mechanisms of Human Disuse Atrophy - Bass, Joseph J.; Hardy, Edward J. O.; Inns, Thomas B.; Wilkinson, Daniel J.; Piasecki, Mathew; Morris, Robert H.; Spicer, Abi; Sale, Craig; Smith, Ken; Atherton, Philip J.; Phillips, Bethan E. (Frontiers in Physiology, 2021)
Objective: Disuse atrophy (DA) describes inactivity-induced skeletal muscle loss, through incompletely defined mechanisms. An intriguing observation is that individual muscles exhibit differing degrees of atrophy, despite exhibiting similar anatomical function/locations. We aimed to develop a novel experimental paradigm to investigate Atrophy Resistant tibialis anterior (TA) and Atrophy Susceptible medial gastrocnemius (MG) muscles (ARAS) with a future view of uncovering central mechanisms. Method: Seven healthy young men (221y) underwent 15-days unilateral leg immobilisation (ULI). Participants had a single leg immobilised using a knee brace and air-boot to fix the leg (75° knee flexion) and ankle in place. Dual-energy X-ray absorptiometry (DXA), MRI and ultrasound scans of the lower leg were taken before and after the immobilisation period to determine changes in muscle mass. Techniques were developed for conchotome and microneedle TA/MG muscle biopsies following immobilisation (both limbs), and preliminary fibre typing analyses was conducted. Results: TA/MG muscles displayed comparable fibre type distribution of predominantly type I fibres (TA 67±7%, MG 63±5%). Following 15-d immobilisation, MG muscle volume (–2.8±1.4%, p<0.05) and muscle thickness decreased (-12.9±1.6%, p<0.01), with a positive correlation between changes in muscle volume and thickness (R2 0.31, p=0.038). Importantly, both TA muscle volume and thickness remained unchanged. Conclusion: The use of this novel “ARAS” paradigm provides an effective and convenient means by which to study the mechanistic basis of divergent DA susceptibility in humans, which may facilitate new mechanistic insights, and by extension, mitigation of skeletal muscle atrophy during human DA.